Using eDNA to develop a national citizen science-based monitoring programme for the great crested newt (Triturus cristatus). (March 2015) - Biggs, Jeremy; Ewald, Naomi; Valentini, Alice; Gaboriaud, Coline; Dejean, Tony; Griffiths, Richard A.; Foster, Jim; Wilkinson, John W.; Arnell, Andy; Brotherton, Peter; Williams, Penny; Dunn, Francesca
Highlights: We evaluated the use of eDNA methods for monitoring great crested newts in the UK. eDNA was more effective than standard methods in detecting newt presence or absence. Volunteers were able to collect eDNA samples successfully with only limited training. A national volunteer eDNA monitoring programme is feasible for great crested newts. We suggest that eDNA could be used in volunteer biodiversity surveys more generally. Abstract: The use of environmental DNA (eDNA) is rapidly emerging as a potentially valuable survey technique for rare or hard to survey freshwater organisms. For the great crested newt ( Triturus cristatus ) in the UK, the substantial cost and manpower requirements of traditional survey methods have hampered attempts to assess the status of the species. We tested whether eDNA could provide the basis for a national citizen science-based monitoring programme for great crested newts by (i) comparing the effectiveness of eDNA monitoring with torch counts, bottle trapping and egg searches and (ii) assessing the ability of volunteers to collect eDNA samples throughout the newt's UK range. In 35 ponds visited four times through the breeding season, eDNA detected newts on 139 out of 140 visits, a 99.3% detection rate. Bottle traps, torch counts and egg searches were significantly less effective, detecting newts 76%, 75% and 44% of the time. eDNA was less successful at predicting newt abundance being positively, but weakly, correlated with counts of the number of newts. Volunteers successfully collected eDNA samples across the UK with 219 of 239 sites (91.3%) correctly identified as supporting newts. 8.7% of sites generated false negatives, either because of very small newt populations or practical difficulties in sample collection. There were no false positives. Overall, we conclude that eDNA is a highly effective survey method and could be used as the basis for a national great crested newt monitoring programme.